Direct Observation of Metal Oxide Nanoparticles Being Transformed into Metal Single Atoms with Oxygen‐Coordinated Structure and High‐Loadings. (4th June 2021) - Liu, Jian; Cao, Changyan; Liu, Xiaozhi; Zheng, Lirong; Yu, Xiaohu; Zhang, Qinghua; Gu, Lin; Qi, Ruilian; Song, Weiguo
Abstract: Direct conversion of bulk metal or nanoparticles into metal single atoms under thermal pyrolysis conditions is a highly efficient and promising strategy to fabricate single‐atom catalysts (SACs). Usually, nitrogen‐doped carbon is used as the anchoring substrate to capture the migrating metal ion species at high temperatures, and stable isolated SACs with nitrogen coordination are formed during the process. Herein, we report unexpected oxygen‐coordinated metal single‐atom catalysts (Fe‐, Co‐, Ni‐, Mn‐SACs) with high loadings (above 10 wt %) through direct transformation of metal oxide nanoparticles (Fe‐, Co‐, Ni‐, Mn‐NPs) in an inert atmosphere at 750 °C for 2 h. The atomic dispersion of metal single atoms and their coordinated structures were confirmed by aberration‐corrected scanning transmission electron microscopy and X‐ray absorption fine structures. In addition, the dynamic process of nanoparticles to atoms was directly observed by in situ transmission electron microscopy. The as‐prepared Fe SAC exhibited high activity and superior selectivity for catalytic oxidation of benzene to phenol with hydrogen peroxide. Abstract : Unexpected oxygen‐coordinated metal single‐atom catalysts (Fe‐, Co‐, Ni‐, Mn‐SACs) with high loadings (above 10 wt %) through direct transformation of metal oxide nanoparticles (Fe‐, Co‐, Ni‐, Mn‐NPs) in an inert atmosphere are directly observed.